Effect of Adaptation Gain in Model Reference Adaptive Controlled Second Order System - Swarnkar, P.; Jain, S.; Nema, R. K. (Engineering, Technology & Applied Science Research, 2011)
Adaptive control involves modifying the control law used by the controller to cope with the fact that the parameters of the system being controlled change drastically due to change in environmental conditions or in system itself. This technique is based on the fundamental characteristic of adaptation of living organism. The adaptive control process is one that continuously and automatically measures the dynamic behavior of plant, compares it with the desired output and uses the difference to vary adjustable system parameters or to generate an actuating signal in such a way so that optimal performance can be maintained regardless of system changes. Nature of adaptation mechanism for controlling the system performance is greatly affected by the value of adaptation gain. It is observed that for the lower order system wide range of adaptation gain can be used to study the performance of the system. As the order of the system increases the applicable range of adaptation gain becomes narrow. This paper deals with application of model reference adaptive control scheme to second order system with different values of adaptation gain. The rule which is used for this application is MIT rule. Simulation is done in MATLAB and simulink and the results are compared for varying adaptation mechanism due to variation in adaptation gain.